Perbedaan Sikap Masyarakat Awam Terlatih dan Tidak Terlatih terhadap TindakanHands Only CPR di Komunitas Surfer Kabupaten Lombok Barat - I Made Eka Santosa; Fachmirahman; Alwan Wijaya; Wahyu Cahyono; Ni Made Sumartyawati (LPPM STIKES Mataram, 2023)
Introduction: Cardiac arrest is a sudden loss of heart function in someone who has or has never been diagnosed with heart disease which can be fatal if not treated immediately. Cardiac arrest can occur anywhere, both outside the hospital and inside the hospital. Heart disease is also known to be very deadly so survival is much more likely when cardiac arrest victims receive Cardiopulmonary Resusictation (CPR) immediately from a bystander (layperson). Purpose: The aim of the research was to see the differences in the attitudes of trained and untrained laypeople towards Hands Only CPR in the West Lombok Surfer Community. Methods: The research design uses descriptive analytics. The population is 96 surfer members. The sampling technique used was total sampling. The sample used as respondents was 78 people. The research instrument used a questionnaire, and data analysis used the Independent T-Test. Result: The research results showed that of the 78 respondents, the attitude of trained lay people towards Hands Only CPR was in the good category, namely around 76.1%. Meanwhile, the attitude of untrained lay people is in the less than 87.5% category. Independent T-Test statistical test p value 0.000 < 0.05. Suggestions: for future researchers are that they can carry out further research related to anemia in patients with kidney failure. Key Words : cardiac arrest, trained layperson, untrained layperson